Variation in heart-rate profile during a prolonged, submaximal swim bout - Goss, C. S.; Greenshields, J. T.; Brammer, C. L.; Kojima, K.; Wright, B. V.; Chapman, R. F.; Stager, J. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To describe the heart-rate (HR) response during a prolonged, submaximal, multirepetition swimming bout (ie, typical early-season swimming training), as there is currently little or no literature on this topic. Methods: A total of 12 collegiate swimmers were instructed to complete sixty 91.4-m (100-yd) freestyle repetitions at their fastest sustainable pace, allowing between 5 and 10 seconds of rest between repetitions. Each swimmer was outfitted with a cardiotachometer, which monitored HR throughout the trial. Completion time (CT) was also recorded for each repetition. Individual means of HR and CT were calculated, and linear mixed models were used to determine the trend across repetitions and between- and within-subject SD for HR and CT. Results: The mean (SD) value for HR was 167.8 (10.8) beats per minute (bpm), for CT was 68.7 (4.1) seconds, and for percentage of best time was 71.2% (4.5%). There was no change (Delta rep 55-6) in HR (-0.1 bpm; 95% confidence interval, -6.8 to 6.6 bpm; P = .97), whereas CT increased (3.0 s; 95% confidence interval, 1.5-4.4 s; P = .001). The between-subjects SD (95% confidence interval) for HR was 12.6 (8.4-19.3 bpm) and for CT was 4.6 (3.1-7.0 s). The within-subject SDs for HR and CT were 4.0 (3.8-4.3 bpm) and 0.9 (0.8-0.95 s), respectively. Conclusions: The inherent individual variability between swimmers in HR during training suggests that coaches carefully consider the common practice of prescribing workout intensity using rigid HR zones.